Structural Non-Structural Protein-1 Virus Dengue of Risk Factors on Functional Interference Hepar (Medico Legal Update, 2020)
The causes of hepatic damage to DHF are mixed. Dengue virus can infect the liver and cause damage.Histopathology of the liver in cases of fatal dengue shows that hepatocytes and Kupffer cells can be thetarget of viral replication and there is involvement of apoptotic mechanism. This study aims to determinethe association between dengue virus NS1 protein and degree of clinical manifestation of dengue infectionwith hepatic dysfunction. Blood samples after taking the serum, were examined for dengue virus NS1protein and SGOT and SGPT examinations at the Surabaya Health Laboratory Center. Data analysis usedChi Square, Fisher's Exact, Anava and Dunnet (a = 0.05). The results shows that the correlated variablesignificantly with dengue hemorrhagic manifestation degree was dengue virus NS protein1 (p = 0.047),with correlation strength of 26.8%. Variables significantly correlated with liver dysfunction were degreeof clinical manifestation of dengue fever (p = 0.037) with correlation strength of 33.5% and dengue virusNS protein1 (p = 0.023) with correlation strength of 29.3%. There was a significant relationship betweenthe presence of dengue virus NS1 protein and the incidence of DHF. There was a significant relationshipbetween the presence of dengue virus NS1 protein with hepatic dysfunction (SGOT and SGPT) in denguevirus infection.